Umwelt- und marktorientierte Fernstraßenentwicklung in Deutschland. Strategien für eine konzeptionelle Neuordnung der Bundesverkehrswegebereitstellung. - Hentrich, Steffen (Deutscher Verkehrs-Verl., 2006)
In seinem kürzlich veröffentlichten Sondergutachten "Umwelt und Straßenverkehr" wies der Sachverständigenrat für Umweltfragen (SRU) auf wesentliche Defizite der Verkehrswege- und Raumplanung des Bundes hin. Kernpunkte seiner Reformvorschläge waren dabei eine konzeptionelle Neuordnung der Bundesverkehrswegeplanung, der marktorientierte Neu- und Ausbau von Fernstraßenverbindungen sowie eine konsequente mautbasierte Nutzerfinanzierung dieser Verkehrsprojekte. Im Beitrag wird dieser Reformansatz ausgehend von einer kurzen Problemanalyse der gegenwärtigen Planung und Bereitstellung der Fernstraßeninfrastruktur näher erläutert. difu

The special report "The Environment and Transport by Road" recently published by the SRU (Specially appointed Experts' Council for Environmental Concerns) makes reference to notable shortcomings in the Federal Government's plans for transport routes and urban/regional development. One of the main points covers the recommendation to reappraise concepts of federal trunk route planning, a market-orientated approach to the construction of new - or the expansion of - trunk roads, and the determination to base funding of future projects on road user charges. The article features the discussion of reform proposals by offering a brief analysis of problems associated with current plans and the earmarking of trunk route infrastructure facilities. The aim is to place more emphasis on market orientated arrangements for federal trunk roads by way of separating the financial and politically motivated decision process. Also, aspects of the enhanced economic viability of future transport-related projects should be taken into account more als should be a system of fair road user charges intended to cover the construction and maintenance costs of trunk roads. This is to create the right conditions for an environment that is more suitable for traffic develoment. difu
Keywords: Verkehr; Bundesverkehrswegeplan; Neuordnung; Verkehrsplanung; Verkehrsnachfrage; Bundesstraße; Straßenplanung; Verkehrsinfrastruktur; Autobahn; Bundesfernstraßenbau; Finanzierung; Fernstraße; Infrastrukturkosten; Maut